Rational Design of Membrane Proximal External Region Lipopeptides Containing Chemical Modifications for HIV-1 Vaccination - Venditto, Vincent J. (American Society for Microbiology, 2013)
The inability to generate broadly neutralizing antibody (bnAb) responses to the membrane proximal external region (MPER) of HIV-1 gp41 using current vaccine strategies has hampered efforts to prevent the spread of HIV. To address this challenge, we investigated a novel hypothesis to help improve the anti-MPER antibody response. Guided by structural insights and the unique lipid reactivity of anti-MPER bnAbs, we considered whether amino acid side chain modifications that emulate hydrophilic phospholipid head groups could contribute to the generation of 2F5-like or 4E10-like neutralizing anti-MPER antibodies. To test this hypothesis, we generated a series of chemically modified MPER immunogens through derivatization of amino acid side chains with phosphate or nitrate groups. We evaluated the binding affinity of the chemically modified peptides to their cognate monoclonal antibodies, 2F5 and 4E10, using surface plasmon resonance. The modifications had little effect on binding to the antibodies and did not influence epitope secondary structure when presented in liposomes. We selected five of the chemically modified sequences to immunize rabbits and found that an immunogen containing both the 2F5 and 4E10 epitopes and a phosphorylated threonine at T676 elicited the highest anti-peptide IgG titers, although the high antipeptide titers did not confer higher neutralizing activity. These data indicate that side chain modifications adjacent to known neutralizing antibody epitopes are capable of eliciting antibody responses to the MPER but that these chemically modified gp41 epitopes do not induce neutralizing antibodies.